Trade Secrets: A Moyers Report
Innovations in chemistry over the past 50 years have produced thousands of man-made chemicals. The majority of Americans believe that the government is making sure that they are protected from harmful substances, but journalist Bill Moyers and producer Sherry Jones raise the question whether they are right to believe so. The result is an investigation of the history of the chemical revolution and the companies that drove it – and how companies worked to withhold vital information about the risks from workers, the government, and the public. The filmmakers rely on an archive of documents the public was never meant to see – documents that were not disclosed at the time and which reveal the industry's early knowledge that some chemicals could pose dangers to human health. The film which features interviews with historians, public health officials and workers is followed by a panel discussion moderated by Bill Moyers.